Living the body : embodiment, womanhood and identity in contemporary India - Thapan, Meenakshi (Sage Publications India ; SAGE, 2009)
This book explores the development of a sociology of embodiment in the context of women's lives in contemporary, urban India. Through a critical analysis of gender and class, the author unravels the complexities that are intrinsic to the multi-layered and fluid construction of woman's identity in relation to embodiment.